Great Expectations, Financialization, and Bank Bailouts in Democracies. (July 2020) - Chwieroth, Jeffrey M.; Walter, Andrew
Accelerating financialization and rising societal wealth have meant that democratic governments increasingly provide bailouts following banking crises. Using a new long-run data set, we show that despite frequent and virulent crises before World War II, bank bailouts to protect wealth were then exceptionally rare. In recent decades, by contrast, governments have increasingly opted for extensive bailouts—well before the major interventions of 2007–2009. We argue that this policy shift is the consequence of the "great expectations" of middle-class voters overlooked in existing accounts. Associated with the growing financialization of wealth, rising leverage, and accumulating ex ante financial stabilization commitments by governments, these expectations are suggestive of substantially altered policy preferences and political cleavages. Since the 1970s, when severe banking crises returned as an important threat to middle-class wealth, this "pressure from below" has led elected governments to provide increasingly costly bailouts with no historical precedent.